Activating omega-6 polyunsaturated fatty acids and inhibitory purine nucleotides are high affinity ligands for novel mitochondrial uncoupling proteins UCP2 and UCP3 - Zackova, Markéta; Skobisová, Eva; Urbánková, Eva; Jezek, Petr (The Journal of biological chemistry, 2003)
UCP2 (the lowest Km values: 20 and 29 microm, respectively) for omega-6 polyunsaturated FAs (PUFAs), all-cis-8,11,14-eicosatrienoic and all-cis-6,9,12-octadecatrienoic acids, which are also the most potent agonists of the nuclear PPARbeta receptor in the activation of UCP2 transcription. omega-3 PUFA, cis-5,8,11,14,17-eicosapentaenoic acid had lower affinity (Km, 50 microm), although as an omega-6 PUFA, arachidonic acid exhibited the same low affinity as lauric acid (Km, approximately 200 microm). These findings suggest a possible dual role of some PUFAs in activating both UCPn expression and uncoupling activity. UCP2 (UCP3)-dependent H+ translocation activated by all tested FAs was inhibited by purine nucleotides with apparent affinity to UCP2 (reciprocal Ki) decreasing in order: ADP > ATP approximately GTP > GDP >> AMP. Also [3H]GTP ([3H]ATP) binding to isolated Escherichia coli (Kd, approximately 5 microm) or yeast-expressed UCP2 (Kd, approximately 1.5 microm) or UCP3 exhibited high affinity, similar to UCP1. The estimated number of [3H]GTP high affinity (Kd, <0.4 microm) binding sites was (in pmol/mg of protein) 182 in lung mitochondria, 74 in kidney, 28 in skeletal muscle, and approximately 20 in liver mitochondria. We conclude that purine nucleotides must be the physiological inhibitors of UCPn-mediated uncoupling in vivo.
Keywords: proteiny; adenosintrifosfát; Mitochondria; koenzymy; guanosintrifosfát; Uncoupling Protein 3; Guanosine Triphosphate; ligandy; Liposomes; ubichinon; Fatty Acids, Omega-6; Biological Transport; membránové transportní proteiny; Ligands; iontové kanály; kvasinky; Uncoupling Protein 2; uncoupling protein 3; kyseliny laurové; mitochondriální proteiny; protony; Membrane Transport Proteins; liposomy; Ion Channels; Carrier Proteins; Mitochondrial Proteins; kyseliny mastné omega-6; tritium; biologický transport; kinetika; lidé; Fatty Acids, Unsaturated; Tritium; Humans; uncoupling protein 2; Protons; Ubiquinone; Coenzymes; Adenosine Triphosphate; Yeasts; nenasycené mastné kyseliny; Proteins; Kinetics; transportní proteiny; mitochondrie; Lauric Acids